Long-term outcome and mortality predictors in patients with extremely enlarged left ventricle end-diastolic diameter undergoing cardiac resynchronization therapy. (3rd October 2022) - Mazurek, M; Jedrzejczyk-Patej, E; Lenarczyk, R; Sokal, A; Kotalczyk, A; Kowalska, W; Gumprecht, J; Kowalski, O; Kalarus, Z
Abstract: Background: Data on efficacy of cardiac resynchronization therapy (CRT) and prognosis of CRT recipients with extremely enlarged left ventricular prior to device implantation are scarce. Aim: To determine outcome and mortality predictors in patients with heart failure (HF) and extremely increased left ventricle end-diastolic diameter (LVEDD) treated with cardiac resynchronization therapy. Methods: Study population consisted of 1059 consecutive patients with CRT implanted between 2002 and 2019 in a tertiary care university hospital, in a densely inhabited, urban region of Poland (949 subjects [89.6%] with CRT-D; 110 patients with CRT-P [10.4%]). Results: The median LVEDD before CRT implantation was 68 mm (56–80). We divided all CRT patients into quartiles as per LVEDD: I <61 mm, II 61–67 mm, III 68–73 mm and IV ≥74 mm. During the median follow-up of 1661 days (10th and 90th percentile: 323–3995) mortality rates for quartiles I–IV were 41.2, 49.6, 55.9 and 68.1%, respectively (P<0.001). The LVEDD ≥74 mm (quartile IV) appeared to be an independent risk factor for death (HR 1.29, 95% CI 1.05–1.6, P=0.02). On multivariable analysis, severe mitral regurgitation (MR; HR 1.54, 95% CI 1.1–2.16, P=0.01) and advanced age (HR 1.02, 95% CI 1.01–1.03, P=0.02) were independent risk factors for death in quartile IV. During observation, mortality rate for quartile IV patients aged >65 years and with severe MR was 90%. Exclusion of subjects with severe MR and aged >65 from quartile IV resulted in similar mortality rate (53.1%) as for patients in lower quartiles. Conclusions: Mortality rates in CRT recipients with extremely enlarged LVEDD is significantly higher compared to those with LVEDD <74 mm. CRT offer to HF patients with LVEDD ≥74 mm (and in particular those with accompanying severe MR and aged >65 years) should be very carefully assessed and other HF therapies (i.e. left ventricular assist devices) should be considered, as more than 90% of those die within 4 years since CRT implantation. Funding Acknowledgement: Type of funding sources: None.